Developing and evaluating a model of public involvement and engagement embedded in a national longitudinal study: HealthWise Wales - Townson, Julia; Davies, Jan; Hurt, Lisa; Ashfield-Watt, Pauline; Paranjothy, Shantini (International Journal of Population Data Science, 2021)
Introduction Worldwide large cohort studies have invested in community engagement to promote studies and aidrecruitment. HealthWise Wales, a national population study, aims to create a register of ‘researchready’ participants and provide long-term follow up data on health behaviours, outcomes andwider social and environmental determinants. Public involvement and engagement was key to thedevelopment of HealthWise Wales. We describe how a model for promoting HealthWise Wales wasco-produced with members of the public. Methods Members of the public were invited to take part in a workshop, either in North or South Wales,to discuss public involvement in long-term cohort studies. Information on community engagement,projects that had used the concept of "citizen scientists" to promote involvement, and other largelongitudinal studies was provided to 15 members of the public prior to the meeting. Eight ofthese attended the workshops, to explore the concept of citizen scientist and how it may relateto HealthWise Wales. Results Data from two workshops was used to draft a protocol for involvement that was reviewed and refinedby members of the public. The protocol describes two levels of public involvement, HealthWise WalesChampion or Supporter. The Champion is a more formal role that requires promoting the projectat public events, whereas Supporters pledge to promote the study to friends and family. Trainingwas provided to 17 of the 26 members of the public who had expressed interest in becoming HWWChampions. Twelve trained Champions attended 41 events to promote the study and collect ’consentto contact’ forms from members of the public. Conclusions It is possible to develop a model of community engagement with members of the public to promoteand raise awareness of a national population study in Wales. It is essential that adequate resourceis provided to support the concept.